1980
DOI: 10.4039/ent112793-8
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Aquatic Plants on Colonization of Artificial Ponds by Mosquitoes and Their Insect Predators

Abstract: The aquatic plants Utricularia minor L., Lemna minor L., and Elodea canadensis Rich. in Michx. were tested for their effects on the colonization of artificial ponds by mosquitoes and their predators. During the 11 weeks of sampling there were significantly fewer mosquito eggs, and hence mosquito larvae, in the plant-filled ponds than in plantless control ponds, and more predators in the Utricularia and Elodea ponds than in the plantless and Lemna ponds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 4 publications
(4 reference statements)
1
7
0
2
Order By: Relevance
“…Survival of the second instar larvae as emerged adults related to their initial number, showed that the presence of duck weed reduced the survival pronouncingly (Table 4). The previous results are in agreement with those of Angerilli and Beirne (1980), Hobbs and Molina (1983) and Parsons (1985). The previous results are in agreement with those of Angerilli and Beirne (1980), Hobbs and Molina (1983) and Parsons (1985).…”
Section: Effects Under Laboratory Conditionssupporting
confidence: 92%
See 2 more Smart Citations
“…Survival of the second instar larvae as emerged adults related to their initial number, showed that the presence of duck weed reduced the survival pronouncingly (Table 4). The previous results are in agreement with those of Angerilli and Beirne (1980), Hobbs and Molina (1983) and Parsons (1985). The previous results are in agreement with those of Angerilli and Beirne (1980), Hobbs and Molina (1983) and Parsons (1985).…”
Section: Effects Under Laboratory Conditionssupporting
confidence: 92%
“…Moth pH and salinity were not seemingly limiting colonization of the mosquito in the sewerage water duck free (Table 1). In connection with this point, Angerilli and Beirne (1980) found that pools completely covered with duck weed never contain larvae of culic idae. Duck weed and similar floating plants, Azolla and Wolffia especially when they form dense mats on the water surface limit mosquito production (Smith and Enns, 1967;Hobbs and Molina, 1983).…”
Section: Colonization Of the Mosquito Under Field Conditionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Because some aquatic plant control programs are undertaken to promote mosquito control, it is noteworthy that Angerilli & Beirne (1980) found that there were significantly more egg rafts and mosquito larva in plantless control ponds than in plant-filled ponds they studied in British Columbia. E. canadensis was an important species in these ponds.…”
Section: Relationships With Waterfowl and Furbearersmentioning
confidence: 99%
“…Such conditions have been reported to limit the occurrence of mosquito larvae (Angerilli and Beirne 1980), and may be largely responsible for the paucity of chironomids observed in 1987.…”
Section: Resultsmentioning
confidence: 99%